Les mineurs devant le tribunal de première instance en Martinique (1937-1944) : enjeux et stratégies - Claire Palmiste (Criminocorpus)
While in France the historiography on juvenile delinquency has had a significant development, thanks to the contribution of civil societies such as AHES-PJM, but also thanks to academic work (Henri Gaillac, 1970; Elise Yvorel, 2007; Ludvine Bantigny, Ivan Jablonka, 2009; Sophie Victorien, 2011; Jean-Jacques Yvorel, 2012), in the French Antilles this issue has not been adressed so far, except for Gaston-Jean, Bouvenet, 1936.Relying on Jean-Jacques Yvorel’s definition of juvenile delinquency as a result of social construct, we will examine a register that was kept by the president of the Court of first instance in Fort-de-France. It gives information on the social and economic stakes and the strategies put in place for the management of juvenile delinquency during two successive periods: the end of the inter-war period (1937-1939) and the time when Martinique was placed under the authority of the Admiral Robert, the representative of the Vichy regime (1940-1943). This paper gives an account of the complex interaction between ethnicity, gender, class and the necessity of maintaining order within a colonial context when the judge had to take a decision regarding a youngster’s offense. Knowing the significance of social control and order for the colonial authorities, a necessity that was exacerbated under the Vichy regime, we may question the choice the judge made: protecting society from the juvenile delinquents or protecting and re-educating them.